If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -4r = 10r + 10 Reorder the terms: 3 + -4r = 10 + 10r Solving 3 + -4r = 10 + 10r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-10r' to each side of the equation. 3 + -4r + -10r = 10 + 10r + -10r Combine like terms: -4r + -10r = -14r 3 + -14r = 10 + 10r + -10r Combine like terms: 10r + -10r = 0 3 + -14r = 10 + 0 3 + -14r = 10 Add '-3' to each side of the equation. 3 + -3 + -14r = 10 + -3 Combine like terms: 3 + -3 = 0 0 + -14r = 10 + -3 -14r = 10 + -3 Combine like terms: 10 + -3 = 7 -14r = 7 Divide each side by '-14'. r = -0.5 Simplifying r = -0.5
| (3m-4n-7)-(8m+n-6)= | | 32+5n=75 | | 2y=4x-3 | | 2+11x=12x-6 | | (3m-4n-7)(8m+n-6)= | | y^2-16x-6y+25=0 | | 3(a-2)=9(a+2) | | 9x-15= | | 3=12-3x | | -7h-4=h+4 | | 62-c=42 | | -3b-2a-4c+5b-8a= | | 4d-8=19 | | 4(x-4)-11x= | | 6c-12=48 | | 25h=20h+15 | | 1-2x=16-5x | | 4y+6=-14 | | 9(6x+3)= | | 7x=11x+16 | | 3x+-7=-8 | | 9a-4a+a-10= | | 6w+5=w-35 | | 3(2t^2-5)=t | | -5x+-5=9x | | a^2x^2-8abx+16b^2=0 | | 97-4x=41x+17 | | 9=a(14) | | 11-10x=40-17x | | 10x+35=28x+35 | | -74-9x=7x+22 | | 8p-24+10p=138 |